Specific back pain – effective diagnosis and treatment from the radiologist’s point of view - Stueckle, Christoph Alexander; Haage, Patrick (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
The diagnosis and treatment of specific back pain is important in radiology. Due to the high number of patients suffering from back pain, it is important to provide excellent diagnostic and therapeutic support.Based on a recent literature search and considering the relevant guidelines as well as expert opinions, the aspects of specific back pain important for radiologists in terms of pathogenesis, diagnosis, and treatment are presented.Clinical examination in combination with the medical history provides a valid suspected diagnosis. This should subsequently be verified radiologically. MRI is the most effective cross-sectional diagnostic method for investigating specific back pain. A conventional X-ray on two planes in a standing position can be a useful addition if postural causes are suspected. If the clinical symptoms match the morphological findings, radiological treatment can be carried out for nerve root involvement as well as for inflammatory changes of the facet joints. The improvement in symptoms after radiological therapy is considered good overall; at least a short-term improvement in symptoms can generally be achieved, but no reliable data is available regarding the long-term outcome. Using preparations containing triamcinolone, low dosages should be selected in accordance with the guidelines. Embedding in a multimodal pain therapy treatment concept should be considered.Radiology provides essential diagnostic findings regarding specific back pain. Interventional pain therapy is an effective and safe method of treating proven specific back pain.Diagnostik und Therapie des spezifischen Rückenschmerzes sind ein wichtiges Aufgabenfeld der Radiologie. Aufgrund der hohen Anzahl an erkrankten Patienten ist es wichtig zielgerichtet im Patienteninteresse sowohl diagnostisch als auch therapeutisch zu arbeiten.Auf der Basis einer aktuellen Literaturrecherche unter Beachtung der entsprechenden Leitlinien und Expertenmeinungen werden die für den Radiologen wichtigen Aspekte des spezifischen Rückenschmerzes hinsichtlich, Pathogenese, Diagnostik und Therapie dargestellt.Die klinische Untersuchung liefert in Zusammenschau mit der Anamnese eine valide Verdachtsdiagnose, die radiologisch verifiziert werden sollte. Die MRT ist die zielführendste Schnittbilddiagnostik zur Abklärung von spezifischem Rückenschmerz. Ein konventionelles Röntgen in zwei Ebenen im Stehen kann bei Verdacht auf haltungsbedingte Ursachen sinnvoll ergänzt werden. Wenn die klinische Symptomatik zum bildmorphologischen Befund passt, kann eine radiologische Therapie sowohl bei Nervenwurzelaffektion als auch bei entzündlichen Veränderungen der Facettengelenke erfolgen. Die zu erzielende Beschwerdebesserung ist insgesamt als gut zu bewerten, zumindest eine kurzfristige Beschwerdebesserung lässt sich in aller Regel erreichen, bzgl. des Langzeit-Outcomes liegen keine verlässlichen Daten vor. Bei Anwendung triamcinolon-haltiger Präparate sollten niedrige Dosierungen – entsprechend den Empfehlungen der Leitlinien – gewählt werden. Eine Einbettung in ein multimodales schmerztherapeutisches Behandlungskonzept ist zu erwägen.Die Radiologie liefert beim spezifischen Rückenschmerz eine richtungsweisende Diagnostik und kann durch die interventionelle Schmerztherapie oftmals zu einer schnellen Beschwerdebesserung führen.
Keywords: CT; interventional MR; diagnostic radiology; radiculopathy; back pain; infiltration therapy